Etidronate from Medicine to Endodontics: effects of different irrigation regimes on root dentin roughness - Talita Tartari; Anivaldo Pereira Duarte Junior; Jose Otavio Carrera Silva Junior; Eliza Burlamaqui Klautau; Mario Honorato Silva e Souza Junior; Patricia de Almeida Rodrigues Silva e Souza Junior (University of São Paulo, 2013)
An increase in dentin roughness, associated with surface composition, contributes to bacterial adherence in recontaminations. Surface roughness is also important for micromechanical interlocking of dental materials to dentin, and understanding the characteristics of the surface is essential to obtain the adhesion of root canal sealers that have different physico-chemical characteristics. OBJECTIVES: To evaluate the effects of sodium hypochlorite (NaOCl), ethylenediaminetetraacetic (EDTA), etidronic (HEBP), and citric acid (CA) associated with different irrigation regimens on root dentin roughness. MATERIAL AND METHODS: Forty-five root halves of anterior teeth were used. The root parts were sectioned in thirds, embedded in acrylic resin and polished to a standard surface roughness. Initially, the samples of each third were randomly assigned into 3 groups and treated as follows: G1 - saline solution (control); G2 - 5% NaOCl+18% HEBP mixed in equal parts; and G3 - 2.5% NaOCl. After initial measuments, the G3 samples were distributed into subgroups G4, G5 and G6, which were subjected to 17% EDTA, 10% CA and 9% HEBP, respectively. Following the new measuments, these groups received a final flush with 2.5% NaOCl, producing G7, G8 and G9. The dentin surface roughness (Ra) was determined before and after treatments using a profilometer. The Wilcoxon test (α<0.05) was used to compare the values before and after treatments, and the Friedman test (α<0.05) to detect any differences among root thirds. RESULTS: (i) NaOCl did not affect the surface roughness; (ii) there was a significant increase in roughness after the use of chelating agents (P<0.01); and (iii) only the G3 group showed a difference in surface roughness between apical third and other thirds of the teeth (P<0.0043). CONCLUSION: Only the irrigation regimens that used chelating agents altered the roughness of root dentin.